Metabolic Profiling of the Oil of Sesame of the Egyptian Cultivar ‘Giza 32’ Employing LC-MS and Tandem MS-Based Untargeted Method - Reham Hassan Mekky; Essam Abdel-Sattar; Antonio Segura-Carretero; María del Mar Contreras (Foods, 2021)
Sesame (Sesamum indicum L.) is a global oil crop. Sesame oil has been regarded as functional oil with antioxidant properties in several in vivo studies but little is known about its minor fraction. In this line, this study figures out the profile of the polar fraction of Egyptian cultivar Giza 32 sesame oil (SG32 oil) employing reversed-phase high-performance liquid chromatography coupled with diode array detection and electrospray ionization-quadrupole-time-of-flight-mass spectrometry and tandem MS. The characterization of the sesame oil metabolites depended on the observation of their retention time values, accurate MS, and MS/MS data, with UV spectra, and compared with relevant literature and available standards. Remarkably, 86 metabolites were characterized and sub-grouped into phenolic acids, lignans, flavonoids, nitrogenous compounds, and organic acids. From the characterized metabolites, 72 compounds were previously characterized in SG32 cake, which presented antioxidant properties, and hence it could contribute to SG32 oil antioxidant properties. Further studies are required to state the presence of such phenolics in commercial sesame oils and what of these compounds resist oil refining.